2004
DOI: 10.1002/bit.10903
|View full text |Cite
|
Sign up to set email alerts
|

Flow calorimetry and dielectric spectroscopy to control the bacterial conversion of toxic substrates into polyhydroxyalcanoates

Abstract: The microbial conversion of toxic substrates into valuable products in continuous culture requires the equivalent of a tight rope walk between formation of the desired product and intoxication of the microbial catalyst. The condition of the latter is reflected immediately by changes in heat flow rate and beta-dispersion in an electrical RF field. Therefore, these were applied to the example of the continuous growth-associated synthesis of polyhydroxyalcanoates (PHA) from phenol by the bacterial strain Variovor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Experience with this calorimetric technique has been reported, e.g., by Gustafsson and co-workers [11,12], who studied the energy balance during growth of the yeast Saccharomyces cerevisiae for different periods during batch growth, and by Guan et al [13], Guan and Kemp [14], Kemp and Guan [15], who demonstrated the usefulness of this approach in measuring the feeble heat dissipation rates of animal cell cultures. More recently, Maskow et al [16] used this approach for controlling the conversion of toxic substrates by bacteria.…”
Section: Calorimetric Measuring Techniquesmentioning
confidence: 99%
“…Experience with this calorimetric technique has been reported, e.g., by Gustafsson and co-workers [11,12], who studied the energy balance during growth of the yeast Saccharomyces cerevisiae for different periods during batch growth, and by Guan et al [13], Guan and Kemp [14], Kemp and Guan [15], who demonstrated the usefulness of this approach in measuring the feeble heat dissipation rates of animal cell cultures. More recently, Maskow et al [16] used this approach for controlling the conversion of toxic substrates by bacteria.…”
Section: Calorimetric Measuring Techniquesmentioning
confidence: 99%
“…Recently, a growing number of studies have succeeded in monitoring the heat dissipation of microbial during fermentation by ITC [33][34][35][36][37]. Kemp and his colleagues [23,24] had combined a bioreactor with a flow microcalorimeter to monitor the heat flow rate of the growth of animal cells under the controlled conditions for long cultivation time.…”
Section: Resultsmentioning
confidence: 99%
“…FTIR and NIR spectroscopy could, as mentioned in Section "Substrates", be an alternative to at-line HPLC or gas chromatography for the quantification of overflow metabolites such as acetate, ethanol, or citric acid but might also be considered for determining the amount of recombinant protein produced in real-time (Sellick et al 2010). Reaction heat evolution rates can be determined by microcalorimetric (Maskow et al 2004(Maskow et al , 2006Ma et al 2007) and bench-scale calorimetric devices (van Kleeff et al 1998;Marison et al 1998;Schill et al 1999;Schuler et al 2012) and also by using simple instrumentation such as temperature probes and mass flow meters (Biener et al 2010), particularly at large-scale (Voisard et al 2002).…”
Section: Measurementsmentioning
confidence: 99%